"Say it with stamps" Buy!! Nassau County poster stamps : "What helps Nassau helps you!" - unknown ([New York] : WPA Federal Art Project, Dis. 4, 1936)
Poster for Nassau County Association fund raising drive stamp sale showing the Trylon and Perisphere at the 1939 New York World's Fair.